Performance Arts Medicine - Brandfonbrener, Alice; Lederman, Richard; Sataloff, Robert (London Singular Publishing Group, 1998)
Performing Arts Medicine should be invaluable to both physicians and performing artists. It provides guidelines for physicians interested in learning about and caring for the specialized problems of performers. It also provides information useful and understandable for performers and their teachers. Acquiring such knowledge helps performers understand their bodies and avoid injuries; and it puts them in a much better position to assess the quality of the medical care they receive when health problems occur. Teachers and performers will be well served by learning the principles and facts between covers,, and by participating actively in the acquisition of new knowledge and the further evolution of performing arts medicine.